PUISI LISAN: PEMERKASAAN WARISAN BANGSA MELAYU - Razali, Liliy Salwani; Md. Radzi, Shaiful Bahri (JURNAL MELAYU SEDUNIA, 2019)
Oral poetry is one of the bases of Malay civilization. Oral poetry is one of the earliest Malay literature that exists in its illiterate society, or regard as primitive, a fairy tale, imaginary work. Behind its creation, society is prudent in applying all aspects of their life such as the environment, the atmosphere that appears in their naked eyes in the form of simple and easy language patterns for certain purposes. One of these is an affirmation, facilitates memory, mnemonic device and also a feast for the ears. However, behind the wordplay used in the language verse, there is highly intellectual Malay race thinking. Every poetry creation that exists in an illiterate society has different functions. Hence, the objective of this study is to outline the multifunction of Malay oral poetry and how the function exists in the atmosphere of traditional society. The justification of using poetry as the limitation of the study is because the language of poetry is short and simple compared to the prose that is more complex. Malay oral poetry also exists with its simple, easy poetic language based on the atmosphere and the society’s background. Analysis of the text or oral poetry verses in the book form is evidence of Malay empowerment that brings to the basic form of Malay race.